Get Wheelin' in Westlawn: Mounting a Bicycling Program in a Low-Income Minority Urban Community - Anne Dressel; Michael Steinborn; Keith Holt (MDPI AG, 2014)
Located in Milwaukee, Wisconsin, USA, the Westlawn neighborhood is home to the State of Wisconsin's largest public housing development. Westlawn is a low-income, African-American urban community that suffers from a wide range of health and environmental disparities. A community-based participatory action (CBPA) team was formed to address environmental health issues in Westlawn, and found asthma rates there are among the highest in the State. Decreasing air pollution, and corresponding asthma triggers, became a priority for the community. The CBPA team developed a bicycling program to reduce trips made by car and improve air quality in the Westlawn neighborhood. Input from focus group meetings shaped the development, implementation and expansion of the bicycling program. While the program was originally conceived to address environmental health issues, it provided key findings about how to encourage bicycling in low-income minority urban communities.